Investing online for dummies - Krantz, Matt (John Wiley & Sons, 2013)
Want to take firm control of your investments and reach your financial goals, but baffled by the dizzying array of online tools? Start with this bestselling guide. Investing Online For Dummies, 8th Edition will help you build your portfolio with the latest financial management information, tools, and resources available. This top-notch, incredibly popular guide will help you pick stocks, find an online broker, construct a profitable portfolio, research investment data online, parse risk, analyze stocks and financial statements, and so much more.